Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode Hazard Identification, Risk Assessment, and Risk Control Pada Crew Kapal TUGBOAT TB ADAM TUG 1 - Nana Mardiana; Resi Juariah Susanto (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
Occupational Safety and Health (OSH) is a crucial aspect of tugboat operations due to the high risk of workplace accidents. This study aims to identify potential hazards, assess risk levels, and determine appropriate risk control measures for the crew of TB Adam Tug 1 using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. This research employed a descriptive quantitative approach. Data were collected through observation, interviews, and documentation and analyzed using the HIRARC stages, including hazard identification, risk assessment based on likelihood and severity parameters, and risk control. The results identified eight work activities with potential occupational hazards. Risk assessment indicated that activities on the vessel's deck and towing rope handling were classified as high-risk, with a risk rating of 12, while the remaining activities were categorized as medium-risk, with risk ratings ranging from 6 to 9. Risk control measures included the use of Personal Protective Equipment (PPE), safety briefings, equipment inspections, operational supervision, and the implementation of safe work procedures. The application of the HIRARC method proved effective in identifying workplace hazards, prioritizing risk control measures, and improving the implementation of Occupational Safety and Health (OSH) to minimize workplace accidents during tugboat operations.